Crime and tourism: what the available statistics do or do not tell us. (2017) - Mawby, Rob I.
Tourism has long been recognised as a crime generator. There is considerable evidence that many tourist resorts suffer higher than average crime rates, that tourists are disproportionately victimised, and that tourists often cause crime and disorder problems. This poses a dilemma for cities and towns seeking to expand their tourism industry. However, there is surprisingly little hard data available for resort areas to allow policy makers to develop and evaluate appropriate responses to local problems. This article considers the available sources of data and advocates the importance of creating better measures that can more appropriately inform policy for both criminal justice agencies and destination management organisations (DMOs).